Novas ruralidades no município de Campo do Brito-SE - Souza, Eliene Domingas de (2015)
The changes occurring in rural areas motivate studies of researchers that link the different perspectives of developments in contemporary times. Faced with the changes, there is the complexity and dynamics existing in rural areas. These changes are caused by the advent of technologies to the advancement of scientific technical means and the spread of communication and advancement in the transport system in urban and rural areas. With these social, cultural and economic relations changes were modified, new meanings but also the stays occur. In this sense, it is necessary to understand the changes and continuities perceived in people's way of life, social relationships and work in the agricultural and non agricultural. This work, in order to discuss the issue of new Brazilian rural, has the objective of understanding the rural setting of the city of Campo do Brito, given the changes occurring in the Brazilian countryside. For the realization of the research were adopted the following methodological procedures: literature review; interviews with farmers in rural establishments, with representatives from government agencies, trade unions, associations and traders. Information was also collected from secondary sources, then was held to analyze the data to understand the city studied. Analyses were performed with considering the analysis of the dimensions, social, economic and cultural, therefore, the work is based on geographic category space and the concepts of rurality, new rurality, rural and existing relations again between rural and urban. Observed changes in spatial configuration with the addition of new equipment in agricultural activities, infrastructure of villages lined the permanence and the reinterpretation of the traditions from the existing cultural and religious practices that underpin the identity of the population. Shows a combination of activities and revenues as strategic ways to stay, to continue in rural areas.